2010
DOI: 10.1155/2010/347636
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Dexamethasone versus Hydrocortisone for the Treatment of Children with Congenital Adrenal Hyperplasia

Abstract: Classic congenital adrenal hyperplasia affects approximately 1 in 15,000 children. Current treatment strategies using multiple daily doses of hydrocortisone lead to suboptimal outcomes. We tested the hypothesis that nocturnal administration of dexamethasone will suppress the hypothalamic-pituitary-adrenal axis more effectively than standard hydrocortisone treatment by blocking the inherent diurnal secretion of ACTH. We performed a pilot study of five prepubertal patients comparing CAH control during two 24-hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In prepubertal children hydrocortisone as physiological cortisol is chosen as the first-line treatment. It has the least impact on growth suppression as a short-acting glucocorticoid [14]. In our case, administration of oral hydrocortisone (17.5 mg daily) was discontinued after two months due to the lack of significant improvement of suppression of adrenal androgen production.…”
Section: Discussionmentioning
confidence: 83%
“…In prepubertal children hydrocortisone as physiological cortisol is chosen as the first-line treatment. It has the least impact on growth suppression as a short-acting glucocorticoid [14]. In our case, administration of oral hydrocortisone (17.5 mg daily) was discontinued after two months due to the lack of significant improvement of suppression of adrenal androgen production.…”
Section: Discussionmentioning
confidence: 83%
“…Pharmacokinetics of hydrocortisone and diurnal variation of adrenal products are also essential to consider when understanding optimal dosing intervals. There is remarkable synchronicity in the patterns of ACTH, 17OHP, and androstenedione production, peaking at about 4–10 a.m. [19]. There tends to be a decline in hormones in the afternoon regardless of when hydrocortisone is given [13].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies of diurnal variation show lowest natural 17OHP levels between the hours of 1,600–2,000 [13, 15]. Dauber et al [19] has shown that some patients have a natural decline of 17OHP in the afternoon prior to any dose of HC being given. Therefore, adding another hydrocortisone dose at this time with another peak may be physiologically unnecessary [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…81 Nocturnal administration efficacy was investigated by Dauber and colleagues in five prepubertal children. 82 Dexamethasone given at 1/50 total HC daily dose proved to suppress more efficiently both morning ACTH and adrenal steroids than conventional HC replacement.…”
Section: Standard Glucocorticoid Therapymentioning
confidence: 93%